Pengaruh Belanja Modal dan Belanja Pegawai Terhadap Pendapatan Asli Daerah Pemerintahan Provinsi Jawa Barat - Amanda Zhafiera Maharani; Angelin Sherlina Annundi; Fina Widia Wulansari; Indah Aprilia Susanti; Oryza Ardhiarisca (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2024)
. Capital expenditures and personnel expenditures reflect unique economic and public administration dynamics in the provincial context. Both have a vital role in supporting infrastructure development, public services and inclusive economic growth, especially in West Java Province. The aim of this research is to test whether capital expenditure and employee expenditure have an effect on Regional Original Income. This research uses a quantitative research approach. The data source used in this research is a secondary data source originating from the Regional Financial Information System (SIKD) which is published via the Directorate General of Taxes (DJP) website. The results of this research show that the variables of employee expenditure and capital expenditure have a significant positive effect on Regional Original Income.